Development of Monoringan Media (Environmental Conservation Monopoly) for IPAS Learning in Fifth-Grade Elementary Students - Putri Sofiatul Moala; Tri Nopriana (Universitas Pendidikan Mandalika, 2026)
This study aims to develop and evaluate the validity of MONORINGAN (Environmental Conservation Monopoly) as a learning medium for IPAS instruction among fifth-grade elementary school students. The study employed a Research and Development (R&D) approach based on the Borg and Gall model, encompassing the stages of research and information collecting, planning, and developing the preliminary form of the product. Data were collected through product evaluation questionnaires administered to subject matter experts and media experts. The validation data were analyzed using quantitative descriptive analysis techniques. The results indicate that the developed media achieved a high level of validity, with scores of 93.33% from subject matter experts and 94.17% from media experts, both categorized as highly suitable. These findings suggest that the MONORINGAN media is feasible for use as an instructional tool and has the potential to enhance student motivation and learning outcomes. In particular, the media promotes more active and enjoyable learning experiences, thereby facilitating a deeper understanding of the material. In conclusion, MONORINGAN represents a valid and promising instructional medium for supporting IPAS learning in elementary education.